The effect of institutional quality and capital market on unemployment in selected sub-Sahara African economies - Patrick Omoruyi Eke; Olamilekan Shamsideen Busari (Contemporary Economics, 2024)
This study tests institutional quality and the growth-finance' four-contexts hypotheses by investigating the nexus between institutional quality and capital market relative to labour market growth in seven selected sub-Sahara Africa's capital market economies comprising Nigeria, South-Africa, Mauritius, Kenya, Ghana, Cote d'Ivoire and Zimbabwe. Overtime, the dearth of long-term capital and high unemployment have been inimical to well-being of these economies. Perhaps, given the weakness of the market-mechanism in efficient resource allocation in developing economies, the neo-classists theorized integrated institutional-qualities into market reforms and freedom for capacity as probable antidote to market economic philosophy. The study applied pooled mean group and generalized method of moment techniques to data obtained from the World Bank Indicators from 1990 to 2020. It establishes that capital market, proxied by market capitalization induces employment generation while quality of institution exacerbates unemployment. The interaction between institutional quality and market capitalization however significantly reduces unemployment, which suggests that quality institution may be helpful impact to unemployment reduction. The study thus affirms institutional quality hypothesis and finance led growth theory. The paper recommends market freedom, Governments and Securities and Exchange Commissions should deeply liberalize the capital markets for higher citizens' inclusion towards industrial funding and high-quality job creation; listing requirement should be eased; capital trade-points established in semi-urban centers for market deepening and liquidity.
Keywords: G12; K20; J64; 330; capital market; institutional quality; unemployment